Treatment outcomes for multidrug-resistant tuberculosis in Eastern Taiwan - Chih-Bin Lin; Hung-Chieh Sun; Chen-Yuan Chiang; Che-Wei Wu; Hsu-Wen Chou; Tao-Qian Tang; Jen-Jyh Lee (Tzu Chi Medical Journal)
Objectives: The objective of this study is to evaluate the treatment outcomes of patients with multidrug-resistant tuberculosis (MDR-TB) under special programmatic management in Eastern Taiwan over the past 10 years. Materials and Methods: All newly diagnosed MDR-TB patients and MDR-TB patients enrolled previously with persistent positive cultures were included in this study, from May 2007 to April 2017, in Eastern Taiwan. A panel of pulmonologists designed the initial MDR-TB regimens. Subsequently, regimens were adjusted according to drug susceptibility test results for second-line drugs. Mobile teams were organized for treatment support, and several measures were adapted to safeguard effective treatment support. Results: A total of 178 patients with bacteriological confirmed pulmonary MDR-TB were identified, of whom 167 had treatment outcomes when the study was conducted. Of these 167 patients, 120 (71.9%) were cured, 11 (6.5%) completed therapy (78.4% had successful treatment), 25 (15.0%) died, 9 (5.4%) had treatment failure, none were transferred out, and 2 (1.2%) were lost to follow-up. Surgery was performed on 8 (4.8%). Conclusions: This is an analysis of the treatment outcomes after adopting the Directly Observed Treatment, Short-course Plus program to treat MDR-TB patients in Eastern Taiwan. We had a low proportion of loss-to-follow-up, resulting in a high treatment success rate. This program serves as an effective model in providing quality care to patients with MDR-TB.